2022
DOI: 10.3390/jcm11071888
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Lift Associated with Leucocyte-Platelet-Rich Fibrin (Second Generation) for Bone Gain: A Systematic Review

Abstract: The purpose of this systematic review was to analyze sinus lifting procedures and to compare the efficiency of this treatment associated with the second generation of platelet-rich fibrin related to its effects on bone gain and to clarify the regenerative efficacy in sinus lift procedure, whether alone or as a coadjutant to other bone graft materials. The PICOT question was, “In clinical studies with patients needing a maxillary sinus lift (P), does the use of PRF either alone (I) or in conjunction with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our study included more patients who benefitted from the external sinus lift with xenograft materials than implants and L-PRF alone as the sole biomaterial. Although, in the last decade, many studies have been published on the sinus augmentation topic, where the grafting material used was combined with platelet-rich in fibrin concentrate [ 40 44 ], fewer exist that used only L-PRF as a single grafting material [ 45 , 46 ]. For example, the study of Dominiak compared two small groups of patients - only 30 implants in total, xenograft versus PRF, ensuring a 3 year retrospective, but only panoramic evaluation, not CBCT [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study included more patients who benefitted from the external sinus lift with xenograft materials than implants and L-PRF alone as the sole biomaterial. Although, in the last decade, many studies have been published on the sinus augmentation topic, where the grafting material used was combined with platelet-rich in fibrin concentrate [ 40 44 ], fewer exist that used only L-PRF as a single grafting material [ 45 , 46 ]. For example, the study of Dominiak compared two small groups of patients - only 30 implants in total, xenograft versus PRF, ensuring a 3 year retrospective, but only panoramic evaluation, not CBCT [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In attempting to reduce these problems, several alternative biomaterials have been developed. Bone harvested from animals (heterogenous/xenograft biomaterial), especially bovine, has gained popularity (Harduin‐Couto et al., 2022; Monteiro et al., 2022; Otero et al., 2022). Otherwise, this biomaterial only possesses osteoconductive properties (Artzi et al., 2001), and even though it has satisfactory effectiveness, safety, and a high success rate, it presents a low reabsorption rate (Fernández et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In attempting to reduce these problems, several alternative biomaterials have been developed. Bone harvested from animals (heterogenous/xenograft biomaterial), especially bovine, has gained popularity (Harduin-Couto et al, 2022;Monteiro et al, 2022;Otero et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, lateral sinus floor elevation has become a standard surgical procedure for bone augmentation. A variety of materials have been employed for this purpose, including autogenous bone ( 1 , 2 ), allogenic bone ( 3 ), synthetic materials ( 4 , 5 ), recombinant human bone morphogenetic protein-2 delivered on a collagen sponge (BMP-2/collagen) ( 6 ), and autogenous blood-derived materials ( 7 , 8 ). Clinical studies on the BMP-2/collagen device have shown successful bone augmentation, as well as short-term safety and technical feasibility within 16 weeks ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies on the BMP-2/collagen device have shown successful bone augmentation, as well as short-term safety and technical feasibility within 16 weeks ( 6 ). Blood-derived materials which contain thick fibrin fibers with platelets have also been explored ( 7 , 8 ). Animal studies have suggested that the demineralized dentin matrix (DDM) possesses bone-inductive abilities ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%